Ebola virus outbreak, updates on current therapeutic strategies. (11th May 2015) - Elshabrawy, Hatem A.; Erickson, Timothy B.; Prabhakar, Bellur S.
Summary Filoviruses are enveloped negative‐sense single‐stranded RNA viruses, which include Ebola and Marburg viruses, known to cause hemorrhagic fever in humans with a case fatality of up to 90%. There have been several Ebola virus outbreaks since the first outbreak in the Democratic Republic of Congo in 1976 of which, the recent 2013–2015 epidemic in Guinea, Liberia, and Sierra Leone is the largest in recorded history. Within a few months of the start of the outbreak in December 2013, thousands of infected cases were reported with a significant number of deaths. As of March 2015, according to the Centers for Disease Control and Prevention, there have been nearly 25 000 suspected cases, with 15 000 confirmed by laboratory testing, and over 10 000 deaths. The large number of cases and the high mortality rate, combined with the lack of effective Food and Drug Administration‐approved treatments, necessitate the development of potent and safe therapeutic measures to combat the current and future outbreaks. Since the beginning of the outbreak, there have been considerable efforts to develop and characterize protective measures including vaccines and antiviral small molecules, and some have proven effective in vitro and in animal models. Most recently, a cocktail of monoclonal antibodies has been shown to be highly effective in protecting non‐human primates from Ebola virus infection. In this review, we will discuss what is known about the nature of the virus, phylogenetic classification, genomic organization and replication, disease transmission, and viral entry and highlight the current approaches and efforts, in the development of therapeutics, to control the outbreak. Copyright © 2015 John Wiley & Sons, Ltd.